Design and Development of a Web-Based Mosque Management Information System: A Case Study of Darul Amal Mosque - Azmi, Meri; Sonatha, Yance; Kirana, Salsabila Okta; Idmayanti, Rika; Afyenni, Rita (invotek, 2024)
Many mosques in Indonesia face challenges in managing their operational activities, such as construction donations, donations to orphans, funeral donations, and religious assemblies as well as other financial administration. Conventionally, the recording of these activities is still done manually through financial recording in books and socializing the information using loudspeakers or utilizing mosque bulletin boards. To overcome these limitations, this research proposes the development of a Web-based Mosque Management Information System that aims to improve operational efficiency, transparency, and accessibility. The system was developed by taking a case study at Darul Amal Mosque which is a mosque in West Sumatra, Indonesia. The system was developed using PHP programming language and Laravel framework, with an online donation feature that allows donors to make donations without the need to be physically present. The research successfully developed a mosque management platform as expected. And it has been proven that a centralized and easily accessible online management process facilitates financial management, improves services to worshipers and donors, and provides better accountability in mosque operations.